Gamma-Ray Burst Jets and their Radio Observations. (2014) - Granot, Jonathan; van der Horst, Alexander J.
Abstract: Radio observations play a key role in studying the jets that power GRBs, the most luminous cosmic explosions. They are crucial for determining the GRB jet energy, the external density, and the microphysical parameters of relativistic collisionless shocks, from afterglow broadband modeling. Radio image size measurements are rare, but provide extremely useful information. The "radio flare" peaking after ~1 day helps constrain the magnetisation and magnetic-field structure of GRB outflows. This review discusses the current observational and modeling status, focusing on the afterglow and outlining prompt radio emission searches, along with recent theoretical progress in GRB jet dynamics, focusing on magnetic acceleration, jet propagation inside a massive star progenitor (for long GRBs), the reverse shock, and the late afterglow. Great progress has been made in our understanding of magnetic acceleration, collimation and later sideways expansion of GRB jets, with interesting implications for the prompt, reverse shock, and afterglow emission. We outline how theory and observations were combined to study GRB jet physics and their immediate environment. Finally, potential paths are suggested for combining theory and observations to achieve greater progress, and some prospects for the future are discussed in light of the expected improvements in observational capabilities and theoretical advances.